ChemInform Abstract: When Aryldiazonium Salts Meet Vinyl Diazoacetates: A Cobalt‐Catalyzed Regiospecific Synthesis of N‐Arylpyrazoles. Issue 48 (2nd December 2014) - Guo, Haiheng; Zhang, Daming; Zhu, Chenghao; Li, Jian; Xu, Guangyang; Sun, Jiangtao
Abstract The cobalt‐catalyzed coupling reaction of vinyl diazoacetates and aryl diazonium salts affords arylpyrazoles.